The application of forage densification technologies to feeding systems for small ruminant production in the Caribbean : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, Manawatū, New Zealand - Jack, Heidi (Massey University, 2021)
Determining the potential of densified forage as a prospective substitute to commercial feed in small ruminant production systems in the Caribbean is critical. This may lead to the development of more self-sufficient feeding systems which incorporate more locally available ingredients and reduce the dependence on imported commercial feeds. There is currently a lack of information on the use of, or effect of, densified forage on performance in regional small ruminant production. Additionally, information is limited on the nutritive value of prospective forages, to which these technologies can be applied. Therefore, the aims of the thesis were to 1) determine the nutritive value of a range of tropical forages in the Caribbean that are used in regional small ruminant production systems; 2) determine the effect of densified diets comprising different levels of forage on intake in growing lambs; and 3) determine the effect of densified diets comprising forage on growth performance and digestibility in lambs. The results of the thesis showed that there is a range of forages of varying nutritive value that can be used to develop more sustainable feed systems for small ruminants in the Caribbean. Further, the results of the thesis showed that when Trichanthera gigantea (an abundantly available forage) was densified and fed to growing lambs, it resulted in similar intakes, digestibility and growth performance in growing lambs to that of commercial concentrates. The findings of the research can be used as a platform for future studies on the application of densification technologies to feeding systems for small ruminants in the Caribbean.
Keywords: Sheep; Goats; Feeding and feeds; Caribbean Area; Forage plants; Pelleted feed; 300303 Animal nutrition